The uses of idolatry - Cavanaugh, William T. (Oxford scholarship online, 2024)
Through deep explorations of nationalism and consumer culture, 'The Uses of Idolatry' presents a sympathetic but critical account of how and why we sacrifice ourselves and others to gods of our own design.